2022
DOI: 10.3126/bibechana.v19i1-2.46396
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of ZnO Nanoparticles by Chemical Method and its Structural and Optical Characterization

Abstract: In this report, ZnO nanoparticles (NPs) was synthesized by chemical method using Zinc Acetate dehydrate [Zn(CH3COO)2.2H2O)] as precursors and Ethanol and distilled water as solvent. Sodium hydroxide (NaOH) was used to maintain the pH and helps to establish the NPs. The NPs are characterized by XRD, UV-visible spectroscopy and SEM image analysis. The XRD characterization gives the polycrystalline nature of ZnO NPs with the size ~23 nm and ~27 nm calculated by Scherrer’s method and Williamson–Hall method respect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…This indicates that the polycrystalline nature of the film. Here it is observed that there are three main peaks in the X-ray diffraction pattern which are (100), (002) and (101) which indicate that the film are polycrystalline and randomly orientated [10,15]. The polycrystallinity is expected due to the lack of epitaxial relationship between ZnO and the glass substrate.…”
Section: Resultsmentioning
confidence: 84%
See 1 more Smart Citation
“…This indicates that the polycrystalline nature of the film. Here it is observed that there are three main peaks in the X-ray diffraction pattern which are (100), (002) and (101) which indicate that the film are polycrystalline and randomly orientated [10,15]. The polycrystallinity is expected due to the lack of epitaxial relationship between ZnO and the glass substrate.…”
Section: Resultsmentioning
confidence: 84%
“…One of the big challenges in present transistor technology is to increase the maximum attainable carrier density for high performance of the device. The chemical doping to increase the charge carrier is not suitable due to its unnecessary complexity in the physical properties of the material [9,10]. Conventional metal dielec-tric gates have relatively low dielectric constants and have the limitation of charge density accumulation [11].…”
Section: Introductionmentioning
confidence: 99%
“…Materials having very close band gap can show the homojunction at the interface [8]. Zinc oxide (ZnO) has been widely investigated as a promising material for light emitting devices, UV photo detectors, chemical and biological sensor [9][10][11][12]. The lack of p-type electrical conductivity in ZnO emphasizes the importance of the study of hybrid heterojunctions [13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, the spherical nanoparticle (NP) of the desired radius is selected by applying the same statistical procedure. A nanometer-sized particle ranges in size from 1 nm to 100 nm [7,8]. NP serves as distinct units for investigating their physical properties and transport behavior.…”
Section: Introductionmentioning
confidence: 99%